When God's voice is heard the power of preaching - Green, Christopher; Jackman, David (Leicester, UK IVP, 2003)
Includes bibliographical references.
First published 1995. Contributors include John R.W. Stott, Peter F. Jensen, J.I. Packer, Edmund P. Clowney, Philip D. Jensen, D.A. Carson...[et.al.]
Keywords: Preaching